Berberine ameliorates chronic relapsing dextran sulfate sodium-induced colitis in C57BL/6 mice by suppressing Th17 responses. (August 2016) - Li, Yan-hong; Xiao, Hai-tao; Hu, Dong-dong; Fatima, Sarwat; Lin, Cheng-yuan; Mu, Huai-xue; Lee, Nikki P.; Bian, Zhao-xiang
Graphical abstract: Abstract: Ulcerative colitis (UC) is an increasingly common condition particularly in developed countries. The lack of satisfactory treatment has fueled the search for alternative therapeutic strategies. In recent studies, berberine, a plant alkaloid with a long history of medicinal use in Chinese medicine, has shown beneficial effects against animal models of acute UC. However, UC usually presents as a chronic condition with frequent relapse in patients. How berberine will act on chronic UC remains unclear. In the present study, we adopted dextran sulfate sodium (DSS)-induced chronic relapsing colitis model to assess the ameliorating activity of berberine. Colitis was induced by two cycles of 2.0% DSS for five days followed by 14 days of drinking water plus a third cycle consisting of DSS only for five days. The colitis mice were orally administered 20 mg/kg berberine from day 13 onward for 30 days and monitored daily. The body weight, stool consistency, and stool bleeding were recorded for determination of the disease activity index (DAI). At the end of treatment, animals were sacrificed and samples were collected and subjected to histological, RT-qPCR, Western blot, and LC–MS analyses. Lymphocytes were isolated from spleens and mesenteric lymph nodes (MLN) and cultured for flow cytometry analysis of IL-17 secretion from CD4 + cells and the Th17 cell differentiation. Results showed that berberine significantly ameliorated the DAI, colon shortening, colon tissue injury, and reduction of colonic expression of tight junction (TJ) protein ZO-1 and occludin of colitis mice. Notably, berberine treatment pronouncedly reduced DSS-upregulated Th17-related cytokine (IL-17 and ROR-γt) mRNAs in the colon. Furthermore, the mRNA expression of IL-6 and IL-23, and the phosphorylation of STAT3 in colon tissues from DSS-treated mice were pronouncedly inhibited by berberine. Moreover, the up-regulation of IL-17 secretion from CD4 + cells of spleens and MLNs caused by DSS were significantly reversed by berberine treatment. Furthermore, Th17 cell differentiation from naive CD4 + cells isolated from above DSS colitis mice were suppressed by berberine in a concentration-dependent manner. In summary, we demonstrated for the first time that berberine reduced the severity of chronic relapsing DSS-induced colitis by suppressing Th17 responses. The demonstration of activity in this mouse model supports the possibility of clinical efficacy of berberine in treating chronic UC.